Some conceptual aspects and approaches to the analysis of the Malaysian palm oil export marketing strategy / Arshad Hashim - Hashim, Arshad (Universiti Teknologi MARA Cawangan Pahang, 1995)
This paper seeks to examine some of the conceptual approaches to assess the impact of the deployment of an export marketing strategy for Malaysia palm oil in a large number of importing countries. The conceptual analyses of structural changes in the expanding global market (i.E, consumer demand analysis. competition in external environment) and a regression analysis if promotional and other factors affecting import demand curve for Malaysian palm oil are among the suggested approaches highlighted in this paper. Some analytical results based the above mentioned approached from the studies of Hashim (1994,1994a and 1995) are presented and discussed as examples. The paper concluded that conceptual and analytical approaches used in the forementioned studies could be used to assess the impact of export marketing strategy of acommodity of an exporter.